If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 2x + -5 Reorder the terms: 8 = -5 + 2x Solving 8 = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + -2x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + -2x = -5 + 0 8 + -2x = -5 Add '-8' to each side of the equation. 8 + -8 + -2x = -5 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = -5 + -8 -2x = -5 + -8 Combine like terms: -5 + -8 = -13 -2x = -13 Divide each side by '-2'. x = 6.5 Simplifying x = 6.5
| 6x-75x=100 | | (3q-2)(q-7)=0 | | 3/7x=21 | | 4x^2-44x+112= | | (3p-2)(q-7)=0 | | 1/7/8/9 | | 3x+35x=76 | | 12x=2x | | -2+1=3x-5 | | 2/5h-7=12/5h-2h | | w+1/5=7/8 | | (9p-4)(p+9)=0 | | 8=4m-4 | | 4+(-3/5)x=16 | | n/0.6=662/3 | | 2p^3+30p^2-68p= | | 86-2x=60 | | 3/2X5/8 | | v+v+v+v+v+10= | | (8x)+(11x-1)=180 | | x-0.7=8.52 | | 11/2*5/8 | | 6x-21=-12+9x | | P+7/4=37/8 | | 1.5x5/8 | | 0.22y-2.5=0.12y+1-0.6y | | 2y^3+3y^2-50y-75= | | x+x^2=2 | | (4y-8)/(3y)=6 | | 1/2/2 | | (-8c^2+4c+6)-(6c^2+7c-3)= | | -3n+7=-2 |